2015
DOI: 10.1080/00223131.2015.1072482
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effect on CHF enhancement in pool boiling of nanofluids

Abstract: This paper investigates critical heat flux (CHF) in saturated pool boiling for water and TiO 2 nanofluid on a 7 mm diameter vertical copper surface at pressures of 0.1 to 0.8 MPa.The nanofluid was prepared by dispersing 0.002 wt% TiO 2 nanoparticles in deionized water. The CHF of the nanofluid was enhanced about two times over that of water boiling at atmospheric pressure. With the increasing pressure, however, the CHF enhancement with the nanofluid decreases, and almost disappears at 0.8 MPa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…When the boiling process happens, at first, the nucleate boiling happens, where vapor bubbles form at nucleation sites on the heated surface. At this condition, the bubbles detach from the hot surface and move within the fluid, which results in an effective heat transfer [8]. By raising the input heat flux to the fluid, the creation of the bubble increases till a situation where a continuous creation of bubbles makes a layer of vapor that covers the heating surface [9].…”
Section: Introductionmentioning
confidence: 99%
“…When the boiling process happens, at first, the nucleate boiling happens, where vapor bubbles form at nucleation sites on the heated surface. At this condition, the bubbles detach from the hot surface and move within the fluid, which results in an effective heat transfer [8]. By raising the input heat flux to the fluid, the creation of the bubble increases till a situation where a continuous creation of bubbles makes a layer of vapor that covers the heating surface [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dahariya and Betz [6,7] conducted pool boiling experiments for water on horizontal smoothed and sintered-particle wick copper surfaces at pressures ranging from 0 to 413.7 kPa, and the results showed that higher pressure would result in the enhancement of CHF due to the formation of a thermal boundary layer, merging of vapor trains into neighboring trains and modulation of wavelength. Sakashita [8] measured CHF in saturated pool boiling for water and TiO 2 nano uid on a vertical copper surface at pressures of 0.1∼0.8 MPa, and they indicated that CHF of water and a nano uid increased with the increase of pressure, while CHF enhancement of a nano uid would decrease with the increasing pressure. Similar to the abovementioned experimental results, Mudawar and Anderson [9], Alvarino et al [10], and Guan et al [11] also reported that pool boiling heat transfer performance and CHF would be improved with the increasing system pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Although nanofluids exhibit considerably higher critical heat flux (thermal limit) than conventional fluids (such as water) in phase change processes [10], the underlying physics for critical heat flux enhancement in nanofluids is still unclear to the research community. However, the enhanced surface wettability, roughness and wicking effect due to the nanoparticle deposition on a heated surface during the phase change process are considered as possible reasons for high critical heat flux in nanofluids [11,12]. Despite thermal benefits of nanofluids over conventional heat transfer fluids, the former do not exhibit overall hydrothermal characteristics (high dispersion stability and enhanced thermal conductivity).…”
Section: Introductionmentioning
confidence: 99%